The Legal Position of Islam in Indonesia - Karin Yuhsan; Dedi Ratno (Al-Mahkamah: Islamic Law Journal, 2024)
Islamic law is considered the law of God. That is, Islamic law is in the form of Allah's rules that aim to regulate the relationship between humans and God (worship) and the relationship between humans and society, the relationship between humans and daily human activities (muammalah). In Indonesia, Islamic law is adopted in the environment of Religious courts. A woman who has a case in a Religious Court needs to understand the history of its development and its legal sources. In this context, a woman may only litigate in the fields of marriage and inheritance. In this field, a woman does not find legal provisions based on equality between men and women. Instead, she finds legal provisions that are not yet appropriate. The Receptio Theory must continue to exist in the formation of new Indonesian law, because Islamic law is the main factor in the development of law in Indonesia in the form of Indonesian national law. The emergence of the Receptio A Contrario theory means that for Muslims, Islamic law applies, while customary law can apply if it does not conflict with Islamic law. In the development of Indonesian national law, religious law (Islamic Law) is the most dominant basis, where Islamic law plays a very important role in shaping the behavior of Indonesian people. Therefore, Islamic law is an absolute element for the development of Indonesian national law.